(untitled) (Dhaka University Journal of Biological Sciences, 2019)
This work has been conducted to evaluate the water quality of the Buriganga river. In situ water quality parameters and water samples were collected from 10 locations in January 2016 and analyzed later in laboratory for water quality parameters such as pH, Eh, EC, TDS, cations (Na+, K+, Ca2+, Mg2, As3+), anions (Cl-, HCO3-, NO2-, NO3-, SO42-, F-, Br-, PO43-), heavy metals (Cr2+, Pb2+, Zn2+, Cd+2, Fe2+, Mn2+) to see whether or not the level of these parameters are within the permissible limits. The average values of pH, Eh, EC and temperature were 7.31, –214.9 mV, 928.9 μs/cm and 21.4°C, respectively; the average concentration of Na+, K+, Ca2+, Mg2+, and As3+ were 109.62, 13.38, 46.78, 13.98 and 0.018 mg/l, respectively, while the concentrations of Cl-,HCO3-, PO43-, SO42-, NO3-, NO2-, F and Br -were 79, 331.06, 2.22, 84.32, 0.0254, 0.058, 0.224 and 0.073 mg/l, respectively; and the concentration of heavy metals Pb2+, Zn2+, Fe2+ and Mn2+were 0.28, 0.053, 0.17 and 0.23 mg/l, respectively. The study indicates that most of the parameters are within the permissible limits set by Bangladesh water quality standard. The concentrations of K+, Mn2+, and Pb2+ were beyond the permissible limits meaning that that the water of Buriganga is not safe for drinking. The people living beside Buriganga river should be more cautious about using the polluted/contaminated river water. The concerned authorities should take urgent necessary steps to improve the degraded water quality of the river considering the ecological, environmental and economic implications associated with it. Dhaka Univ. J. Biol. Sci. 28(2): 147-158, 2019 (July)